Aspiration to enrol children in Islamic studies: a case of academicians. Issue 4 (14th November 2016) - Islam, Tazul; Zayed, Tareq M.
Abstract : Purpose: A preliminary observation reveals that children of Islamic studies (IS) academicians do not choose IS as their career discipline. In view of this, this paper aims to explore the dimensions of parental attitudes, behaviours, perceptions and aspirations in seeing a future in IS for their children. Design/methodology/approach: Fifteen interviews were conducted to explore the attitude of IS academicians. Findings led us to hypothesize that perceived social recognition explains the maximum variance. Later, 126 academicians were surveyed. Findings: Results of regression analysis rejected the null hypothesis. The parental attitude of IS academicians, their engagement and perceived social recognition significantly predicted their aspiration in enrolling their children in IS. The regression model explained 64 per cent of total variance accounted for IS academicians' career aspirations for their children. This study suggests investigating the socio-cultural and geographical impact on the career aspirations of IS academicians for their children. Originality/value: The findings and results of the study can contribute to educational counselling to guide the counsellors. Further study on this issue may reveal whether IS academicians have plans to modify the curriculum or change their socio-economic status. It should also be examined whether they are doing so as a part of their implicit or explicit strategy.